Energy Literacy and Sustainability Awareness - Breskvar, Uroš (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
Sustainable transitions toward a low-carbon society require a population that understands the fundamental links between energy use, environmental impacts, and everyday decision-making. Energy literacy is a key prerequisite for the effective implementation of sustainability policies and public support for societal change. The aim of this study is to assess the level of energy literacy and sustainability awareness in Slovenia and to position the results within a broader European context. The study is based on a quantitative approach using a structured questionnaire that measures knowledge of energy units, energy consumption, environmental impacts, and the understanding of energy-related technologies. The data were analyzed using descriptive and inferential statistical methods. International comparison was conducted indirectly using secondary indicators, including the Environmental Performance Index, Eurobarometer data, and SULITEST results. The findings indicate that the level of energy literacy in Slovenia is moderate, with notable gaps in understanding systemic and environmental aspects of energy use. In comparison with the European average, Slovenia ranks around the middle, lagging behind countries with a long-standing and systematic integration of sustainability education.